‘A new sense of my former self’ – transforming the self through vocational rehabilitation for people with acquired brain injury - Pia Kold; Hanne Peoples; Hanne Kaae Kristensen; Jesper Larsen Maersk (Scandinavian Journal of Occupational Therapy)
Background Acquired Brain injury (ABI) causes ripples throughout the occupational and social fabric. It enters people’s lives at a significant personal cost, encroaching on people’s sense of self. Vocational rehabilitation is a viable venue to regain control of their life and support them in forming a new sense of self. From an occupational perspective, little is known about how vocational rehabilitation can support people through transforming their sense of self.Aim This study aims to explore how vocational rehabilitation may influence the relationship between sense of self and occupational engagement for persons with ABI. Material and Methods: Six persons with ABI were purposely sampled. Data were collected using semi-structured individual interviews and analysed using a hermeneutic approach.Results The analysis resulted in three themes: a new sense of my former self, engaging in occupations as transformation, and the significance of support.Conclusions Participating in vocational rehabilitation can enable persons with ABI to form a new sense of self. Engaging in occupations and professional support is significant in the transformation process.Significance From an occupational perspective, the knowledge gained in this study stresses the essential role occupational engagement and proper targeted support have for people struggling to return to work after ABI.